2019
DOI: 10.1123/mc.2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Upper to Lower Limb Coordination Dynamics in Swimming Depending on Swimming Speed and Aquatic Environment Manipulations

Abstract: Upper-to-lower limb coordination dynamics in swimming depending on swimming speed and aquatic environment manipulations. Motor control, 1-25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
13
2
Order By: Relevance
“…Thus, upper limb asymmetry does not seem to be related to the level of force, power, or speed developed. A study of swimmers also found no relationship between swimming speed with a higher frequency of arm movements and coordination asymmetry 45 . In the present study, mean arm cranking velocity recorded at the beginning of the test did not differ between LP and HP players.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Thus, upper limb asymmetry does not seem to be related to the level of force, power, or speed developed. A study of swimmers also found no relationship between swimming speed with a higher frequency of arm movements and coordination asymmetry 45 . In the present study, mean arm cranking velocity recorded at the beginning of the test did not differ between LP and HP players.…”
Section: Discussioncontrasting
confidence: 65%
“…A study of swimmers also found no relationship between swimming speed with a higher frequency of arm movements and coordination asymmetry. 45 In the present study, mean arm cranking velocity recorded at the beginning of the test did not differ between LP and HP players. Velocity seemed to increase to a similar extent across participants during the first 10s.…”
Section: Association Between Asymmetry and Performance Variablescontrasting
confidence: 41%
“…According to the first author's main affiliation, most studies are from Australia (14-Interlimb Asymmetries in Swimming 20.3%), followed by Brazil (10-16.7%), followed by France and United States with 7 studies each (11.7%). Seventeen studies (28.3%) reported some funding (3,6,17,19,23,29,38,49,(51)(52)(53)(54)57,65,66,76,77).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…26 Constraints can be manipulated such that the desired movement emerges through a process of self-organisation, rather than via prescriptive (explicit) instruction. For example, Guignard et al 27 manipulated the swimming speed (task constraint) and the fluid flow (environmental constraint) in a flume and reported that elite swimmers adapted their open pool technique to maintain performance by changing their arm-to-leg coordination pattern, without any explicit instruction to do so.…”
Section: Introductionmentioning
confidence: 99%